Effects of compost from food waste on growth of lettuce ( Lactuca sativa Var. Crispa L.) - Aunkamol Kumngen; Jutarut Iewkittayakorn; Usmana Meehae; Sudarat Suwannarat; Sujunya Anuchan; Wilaiwan Chotigeat; Pattamavadee Kunwanlee; Noodchanath Kongchouy; Siwapong Leunram; Seppo Karrila (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Thailand generates approximately 18 million tons of urban food waste per year, which is disposed of with municipal waste and largely goes to landfills. However, this approach not only takes up a large area but also causes environmental problems. The easiest way to manage food waste is by separating it at the source and composting it. Bioaxel Co., Ltd. has developed an innovative approach for composting food waste, with the output commercially marketed as “BA compost”. However, the use of BA compost has not been independently studied.Methods BA compost was mixed with soil in various proportions (0% - 70% v/v) for planting lettuce to find the proper BA proportion. Growth characteristics and nutrient contents were investigated.Results The BA compost improved the soil nutrients. 10% BA compost in soil gave the highest growth parameters among the proportions tested, with the highest root length (21.83 ± 0.83 cm), plant length (30.00 ± 1.00 cm), number of leaves (23.33 ± 1.15 leaves), thickness (12.47 ± 0.57 mm), width of bush (26.33 ± 0.58 mm), fresh plant weight (113.03 ± 1.28 g), dry plant weight (4.58 ± 0.14 g), chlorophyll a and b (0.38 and 0.38 mg/mL), carotenoid (155.28 mg/mL), protein (443.38 μg/mL), carbohydrate (4,321.31 μg/mL) and reducing sugar (683.33 μg/mL).Conclusion BA compost from food waste demonstrated its potential in sustainable food waste management and could be used as a fertilizer. It supports an environmentally closed-loop approach to return the food waste back to the source as plant food.